Science and Skiing VII - Müller, Erich; Kröll, Josef; Lindinger, Stefan; Pfusterschmied, Jürgen; Spörri, Jörg; Stöggl, Thomas (Meyer & Meyer Verlag, 2018)
This book contains the proceedings of the Seventh International Congress on Science and Skiing, which was held at St. Christoph am Arlberg, Tyrol, Austria, in December 2016. The conference was organized and hosted by the Department of Sport Science at the University of Salzburg, Austria. The book offers a broad interdisciplinary spectrum of current high-quality research in Alpine and Nordic skiing and in snowboarding. Four keynote speakers and ninetyseven oral presenters were invited to submit a paper for this volume. The entire scope of relevant topics in skiing is covered by these presentations. In order to maintain the high scientific standard required of this book, the selected papers were subject to peer review and editorial judgment prior to acceptance. In the proceedings of this congress, the keynotes as well as the oral presentations are published.